TANTANGAN DAN PELUANG DINAS SOSIAL DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN JEMBER - Suprianik, Suprianik; Dindi Nur Safitri,; Tika Wulandari,; Tri Linda Arasati, (Juremi: Jurnal Riset Ekonomi, 2024)
Advancements and improvements in basic social services are critical aspects in addressing continually evolving social issues, requiring a holistic and integrated approach. Focusing on the need to ensure access to basic social services in order to create a higher level of well-being and quality of life, this study explores the necessity for innovation in the social welfare system. Through an analysis of the provision of integrated social welfare services in Jember Regency, East Java, this study aims to identify opportunities and obstacles in its implementation, as well as to formulate strategic policies moving forward. Data was obtained from an extensive literature review and analyzed using the SWOT (Strengths, Weaknesses, Opportunities, Threats) framework. Findings indicate that the provision of social welfare services in Jember Regency still faces several challenges, which hinder the achievement of service optimization. Nonetheless, there are significant opportunities that can be leveraged through the development of more supportive policies. This study emphasizes the importance of the role of the Social Services Agency in directing responsive and adaptive social service reforms to the dynamics of social change, both at the local level and more broadly